Boganmeldelser - Inkeri Anttila; Omar H. Kristmundsson; Josef Zila; Janne Flyghed; Jørge Dige Pedersen; Henning Brøndsted; Britta Kyvsgaard; Erlendur S. Baldursson; Jan Pedersen; Anette Storgaard; Vagn Greve; Nils Rekke (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews